Yoga for Geriatric Health: Promoting Health and Well-being in Older Individuals with Yoga (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Geriatrics health is a speciality that spotlights on healthcare of older individuals or the declining stage individuals after midlife. It intends to advance health by forestalling and treating illnesses and inabilities in more established grown-ups. India is in a period of segment change. There has been a sharp expansion in the quantity of older people between 1991 to 2001 and it has been extended that constantly 2050, the quantity of old individuals would ascend to around 324 million. Yoga is an otherworldly science for the coordinated and all encompassing improvement of physical, mental and profound parts of our being. Yoga is amazingly valuable for the older individuals. Yoga improve strength, adaptability and forestalling senescence and age-related illnesses. In antiquated books of Yoga has depicted sufficient plan or Yogic Kriyas that assist proceed with great health with evening in advanced age. It is fundamental Bro concentrate on how Yama, Niyama impacts social, enthusiastic and otherworldly health in the matured, how Asana, Pranayama encourages the body and psyche, how Kriyas, Mudras, Bandhas assemble versatility, fortify all frameworks and postpone maturing. This paper accentuates on Geriatric health care through Yoga. Yoga guarantees that advanced age can be e need endurable as well as pleasurable. In this paper we will study about yoga for geriatric health